Cyclic ring fiber textures in single tungsten fiber-reinforced tungsten composites. Issue 1 (March 2021) - Ciucani, U M; Haus, L; Gietl, H; Riesch, J; Pantleon, W
Abstract: Tungsten fiber-reinforced tungsten composites are considered as plasma-facing material in future fusion reactors. Such composites are obtained by chemical vapor deposition of tungsten on potassium-doped, drawn tungsten wires. In model composites containing single fibers, particular texture types develop due to the cylindrical geometry of the deposition process. The vapor-deposited tungsten layers form a cyclic <100> ring fiber texture with one of the <100> directions pointing radially along the growth direction. The procedure for revealing this non-standard texture type from orientation data obtained by electron backscatter diffraction is presented. Identification of cyclic textures requires carefully chosen acquisition regions as well as a suitable coordinate system for their analysis. It is demonstrated that quite erroneous conclusions about the texture of the layer would be drawn if this is not accounted for properly.